Barriers to Stunting Intervention at a Community Health Center: A Qualitative Study - Rapael Ginting; Ermi Girsang; Megasilvia Sinaga; Putranto Manalu (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is one of Indonesia's most prevalent nutritional problems, with a prevalence rate of 24.4%. In Samosir Regency, the prevalence of stunting remains relatively high at 28.4%. Community health centers are crucial in the community's efforts to accelerate stunting reduction. This study aimed to explore the barriers a community health center faces in implementing the stunting reduction acceleration program. Method: Using a qualitative case study design, the study was conducted at Buhit community health center in Samosir Regency from August to December 2022. The key informants for this study included the community health center leader, head of administration, nutritionist, and midwife. Data were collected through in-depth interviews and document review. The results identified several barriers to the implementation of the Accelerated Stunting Reduction Programme. These barriers encompassed limited staff resources and concurrent positions, the availability and suitability of anthropometric tools, a lack of coordination in planning activities between management and program officers, families' fear of the negative stigma associated with stunting, and low levels of community participation. Farmers who do not comply with safe behavior will have a higher health risk because of the toxicity of pesticides that can be directly inhaled and enter through the pores of the farmers' skin